Perfil das redes sociais no jornalismo público: um estudo sobre a aplicação do manual de orientação para atuação em mídias sociais no IFPE - Lima, Alline Laís Silva (2018)
Faced with the preponderance of technological changes, transformations in the work of the press agents are constants. The old dialogue model based on contact by e-mail or phone calls is losing space for the possibilities brought by digital social platforms. These changes are recognized by the Social Communication Office of the Brazilian Federal Government which created the Orientation Manual for Social Media Activities. This research aims study the case of press agentes from Federal Institute of Pernambuco (IFPE) and the adequacy of its digital social networks, specifically Facebook, with regards of this Orientation Manual. To do so, it performs bibliographic research; normative documents; three interviews with professionals that manage the social digital networks of the Institution; and data analysis of data collected from IFPE’s official social profiles observed in the months of May, June, July and November of 2017, account for 166 publications. As a result, the research presents a diagnosis of IFPE's social networks in the categories of language, information distribution, planning, public dialogue, thematization, visual identity and accessibility, with the application of the Orientation Manual. It also explains the engagement culture of consumers with the advisory services of public bodies. The research involves discussions around the concepts of Public Communication, Post-industrial Journalism, Midiatization, as well as Participation and Connection Cultures. We used the studies of MATOS (2012), FAUSTO NETO (2016); FILHO (2012), RECUERO, BASTO and ZAGO (2015); SHIRKY (2014) and JENKINS (2014), in addition to other authors who also dialogue with the subject studied. We conclude that the professionals follow the main guidelines of the document, despite the limitations of people or/and proper training, that the guidelines in the Manual are most effective and that organizations need to master how to act within digital platforms. For that, it is important to create customized guides and monitor their applicability, suggesting improvements according to the observed performance.